2017
DOI: 10.5897/ajmr2017-8431
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and characterization of Salmonella species isolated from poultry value chains of Gazipur and Tangail districts of Bangladesh

Abstract: The aim of this study was to identify and characterize Salmonella species isolated from poultry value chains of Gazipur and Tangail districts of Bangladesh during the period of October 2015 to May 2016. For this purpose a total of 153 samples (35 chick meconium, 49 cloacal swab, 30 poultry carcass, 14 feed, 16 water, 7 transport swab, 2 floor swab) were collected and were subjected to various cultural, biochemical techniques and polymerase chain reaction (PCR). Furthermore, the isolated Salmonella species were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Fanissa et al (2022) reported a low prevalence of Salmonella species in Surabaya, Indonesia, with a frequency of 11.3%. Other researchers have observed a similar prevalence of Salmonella species; poultry samples 23.53% (Al-Mamun et al 2017); poultry production 37.9% (Mahmud et al 2011), chickens 11.54% (Abd El-Aziz et al 2021) and broiler farms 31.25% (Mridha et al 2020). Prevalence of Salmonella bacteria was detected in 21.3% of chickens analyzed (Telli et al 2022).…”
Section: Discussionsupporting
confidence: 51%
“…Fanissa et al (2022) reported a low prevalence of Salmonella species in Surabaya, Indonesia, with a frequency of 11.3%. Other researchers have observed a similar prevalence of Salmonella species; poultry samples 23.53% (Al-Mamun et al 2017); poultry production 37.9% (Mahmud et al 2011), chickens 11.54% (Abd El-Aziz et al 2021) and broiler farms 31.25% (Mridha et al 2020). Prevalence of Salmonella bacteria was detected in 21.3% of chickens analyzed (Telli et al 2022).…”
Section: Discussionsupporting
confidence: 51%
“…Previously, the prevalence of Salmonella in Bangladesh was found 23.33% in poultry slaughter specimens (Momtaz et al, 2018); 26.6% in chicken cloacal swab, intestinal fluid, egg surface, hand wash, and soil of chicken market samples (Akond et al, 2012); 25.35% in the chicken cloacal swab, eggshells, intestinal contents, liver swabs, broiler meat, and swabs of slaughterhouse (Karim et al, 2017); 35% in broiler farms settings (Alam et al, 2020); 23.53% in poultry samples (Al Mamun et al, 2017); 37.9% in poultry production settings (Mahmud et al, 2011); 31.25% in broiler farm settings (Mridha et al, 2020); 42% in broiler chicken (Sarker et al, 2021) and 65% in frozen chicken meat (Parvin et al, 2020). Successively, Siddiky et al (2021) found the prevalence of Salmonella 8.62% in broiler, 6.89% in sonali and 3.1% in native chicken cecal contents.…”
Section: Discussionmentioning
confidence: 99%